2016
DOI: 10.1590/0103-9016-2015-0427
|View full text |Cite
|
Sign up to set email alerts
|

New opportunities for developing tomato varieties with enhanced carotenoid content

Abstract: The development of varieties with a high content of antioxidant compounds, such as carotenoids, has become a major focus in the marketing of tomato. Several mutants have been used in the development of high pigment varieties, but the significant influence of the environment on carotenoid content and the presence of negative side effects in vegetative growth and yield have limited the success of these variants. Consequently, the identification of alternative sources of variation in the quest for high carotenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, β-carotene content has also exhibited a significant positive association with lipophilic antioxidant capacity (r = 0.86; p < 0.001), having strong antioxidant potential [ 30 ]. Thus, the enhancement of carotenoids contents in tomato using LEDs during post-harvest storage, especially lycopene, is of great interest in the marketing of tomato, which looks for the development of high pigment varieties containing natural antioxidants by the use of different tools, such as breeding programmes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, β-carotene content has also exhibited a significant positive association with lipophilic antioxidant capacity (r = 0.86; p < 0.001), having strong antioxidant potential [ 30 ]. Thus, the enhancement of carotenoids contents in tomato using LEDs during post-harvest storage, especially lycopene, is of great interest in the marketing of tomato, which looks for the development of high pigment varieties containing natural antioxidants by the use of different tools, such as breeding programmes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…These can be considerably high in the accumulation of both sugars and acids. The importance of the interactions has been emphasized in tomato regarding the accumulation of functional compounds, especially vitamin C (Leiva-Brondo et al, 2012), and to a lower extent carotenoids (Leiva-Brondo et al, 2016). This differential behavior may lead to overestimating or underestimating the value of an accession and consequently emphasizes the need to perform screening studies in multienvironmental designs.…”
Section: Discussionmentioning
confidence: 99%
“…In vegetable crops, pre-breeding has been successfully employed for developing health beneficial glucosinolates (3-methylsulphinylpropyl or 4methylsulphinylbutyl) rich genetic stocks in broccoli by marker assisted introgression of QTL1 and QTL2 from Brassica villosa (Sarikamis et al 2006). Leiva-Brondo et al (2016) identified, accessions BGV6195 of Solanum pimpinellifolium, LA1423 of S. Lycopersicon var. cerasiforme and LA3633, a possible hybrid between S. pimpinellifolium and S. lycopersicon var.…”
Section: Pre-breeding For Quality Traits In Vegetable Cropsmentioning
confidence: 99%